Analysis of the Poetry of Labid bin Rabi'ah on the Theory of Tasbih - Asghor , Moch. Ali (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study uses the theory of tasybih science in the Manuscript "Syarh Fī Bayān al-Majāz wa al-Tasybīh wa al-Kināyah" to analyze Labid bin Rabi'ah's poem entitled Fala Jaza'a in Farraqa Alddhahru Bainana from various aspects. This study uses a qualitative research method, namely by analyzing the poem Maa Fii Al-Maqami Lidzi Aqli Wa Lidzi Adabi from aspects of tasybih science. Imam Syafi'I's poetry is the main data source of this study. with supporting data such as articles, books, and research results from reliable journals. Reading and taking notes are data collection methods. In accordance with the definition of literature study, which means research that collects data using library collections. The results of the study indicate that several theories of tasybih science in the Manuscript "Syarh Fī Bayān al-Majāz wa al-Tasybīh wa al-Kināyah" are found in Imam Syafi'i's poem entitled Maa Fii Al-Maqami Lidzi Aqli Wa Lidzi Adabi.